Morphological Characteristics and Similarity Analysis of Cassava (Manihot esculenta Crantz) in Wonosobo, Temanggung, and Magelang Regencies - Sugiyarto Sugiyarto; Tri Suwarni Wahyudiningsih; Ericka Darmawan; Listya Hidayah (Jurnal Biodjati, 2023)
The diversity of cassava in Wonosobo, Temanggung and Magelang districts must be investigated. The objective of the study was to analyze the diversity of cassava based on morphological characteristics. The cassava of each accession was planted in Bandongan, Magelang Regency. Morphological characters observed after six months of planting included apical leaf color, apical leaf hair, leaf lobe shape, petiole color, leaf color, number of leaf lobes, leaf length, leaf width, petiole length, vein color, petiole orientation, color epidermis of stem, color of outer appearance of stem, distance between nodes, stem growth, color of mature branch tip, branching type, tuber, tuber shape, outer tuber skin color, tuber flesh color, and tuber inner skin color. Analysis of the morphological characteristics of cassava is presented in the form of a dendrogram using the MVSP (Multi Variate Statistical Package) version 3.22. The results of the study obtained 39 accessions of cassava which showed different morphological characteristics. The lowest morphological similarity (0.735) was found in Group I only consisted of 2 acquisitions that did not have tubers, namely Red Vegetables and Green Vegetables and Group II ( Groups III and IV) have a similarity of 0.92. The highest similarity was in groups IIIa and IIIb and Groups IVa and IVb have a similarity coefficient value of 0.95. The morphological diversity of 39 accessions is a source of cassava germplasm: 37 accessions are harvested for tubers and 2 accessions areharvested explicitly for leaves as vegetables. This research was useful for the development of cassava-based food industry bioproducts.